STUDYING THE INFLUENCE OF GAMMA RADIATION ON SUPERPARAMAGNETIC Fe₃O₄, NiFe₂O4, MgFe₂O₄ NANOPARTICLES - NGUYEN , MONG GIAO; NGUYEN , THI AI THU; CAO , THI HONG THAI (Nuclear Science and Technology, 2011)
Our works are aimed at studying the influence of gamma radiation on the nano-size magnetic materials. The gamma radiation with 1332 keV and 1174 keV energy was emitted on superparamagnetic Fe3O4, NiFe2O4, MgFe2O4 nanoparticles with various doses. The comparison of properties of the materials before and after radiating was analyzed by hysteresis loop VSM. The microstructure of magnetic nano-particles was determined by SEM, after irradiating the size of magnetic nanoparticles changed about 53 nm, 54 nm, 52 nm for Fe3O4, NiFe2O4, MgFe2O4 ,respectively. Magnetization curves show superparamagnetic behavior with zero coercivity and remanence. With different doses, the gamma radiation can change domain structure of atom and magnetic properties.